Implementasi Akad Muzara’ah Untuk Meningkatkan Kesejahteraan Petani Penggarap Sawah Di Kecamatan Karangmoncol - A Mukhsin Irfangi; Muhammad Hanif Abdilla (CV. Kalimasada Group, 2025)
The problem of unequal access to agricultural land and limited capital for sharecroppers is still a major issue in the development of the agrarian sector in rural areas. This study aims to analyze the implementation of the muzara'ah contract and its contribution to improving the welfare of sharecroppers in Karangmoncol District. Using a qualitative approach with a case study method, data were collected through in-depth interviews, observation, and documentation from sharecroppers, landowners, and community leaders. The results showed that the practice of muzara'ah contract was done verbally without a written agreement, based on trust and social closeness between parties. The profit-sharing system is applied fairly (maro 50:50) after deducting production costs. Although there is a risk of crop failure due to pests and weather, the risk is borne together as a form of justice in sharia principles. This system is proven to provide benefits for both parties-the landowner continues to get the yield from his land, while the farmer can work and earn income without having to provide capital. This study concludes that the muzara'ah contract can be a model of fair and sustainable agricultural cooperation, although it still requires institutional support and increased legal awareness to strengthen its implementation.